Legal Review of Inclusive Education Policy: A Systematic Literature Review 2015-2025 - Kartiko, Ari; Arif, Muhamad; Rokhman, Mauhibur; Ma’arif, Muhammad Anas; Aprilianto, Andika (International Journal of Law and Society, 2025)
Inclusive quality education is essential for national development, aligning with Indonesia's goal to educate intelligent, responsible, and noble citizens without discrimination. Binding legal regulations become the basis for implementing inclusive education that is fair and without prejudice. As for these two research questions: how are the legal rules governing inclusive education in Indonesia and other countries? What are the challenges of implementing inclusive education in Indonesia? Using the systematic literature review research method, with keywords in Indonesian and English, "inclusive education policy" AND "law", and "inclusive education policy" AND "law" AND "Indonesia" in the 2015-2025 period. The researcher obtained the results of 68 articles that were appropriate and complete "full paper", with the final details; articles from Scopus 19 and Google Scholar 49 total of 68 articles. The results of the study show that in terms of legal regulations, inclusive education in Indonesia is much clearer and more binding than in Japan, Malaysia, Vietnam, and Myanmar, only losing to Finland, which is much better in terms of law and implementation. However, Indonesia still has several challenges in implementing inclusive education, such as limited human resources, the need to provide collaboration space for teachers, government and parents, minimal facilities and infrastructure and weak supervision and evaluation. Theoretical implications of clear and binding inclusive education legal regulations start from the definition, rights, obligations, monitoring systems, and sanctions if violations are found compared to other countries.